Analysis of technical efficiency among youth involved in crop production in Njombe Region, Tanzania - Ng'atigwa, A.A.; Hepelwa, A.; Manyong, Victor; Feleke, S. (Informa UK Limited, 2022)
This study aimed to estimate the Technical Efficiency (TE) of youth crop farmers in Njombe Region of Tanzania, and analyze the determinants of technical inefficiency for crops produced. Data were collected from 572 youths in 16 villages of Njombe Region by using a random sampling technique. The Stochastic Production Function (SPF) model analysed technical efficiency among the youth crop farmers. Results show that youth crop farmers in the study region exhibited decreasing returns to scale, as confirmed by the Returns to Scale of 0.275. The mean TE of crops produced was 19.32%, implying that youth farmers still have room to improve their farming efficiency by 80.68% using the same land resources. Most youth farmers had technical efficiency scores from 18.5% to 20.5%. In addition, the estimated SPF model and inefficiency parameters showed that age, land ownership, and extension contact are factors which reduced technical inefficiency in the study region. Thus, more emphasis might focus on enhancing the accessibility of youth farmers to extension services, land ownership, and efficient use of farm inputs might improve the TE of youth crop farmers in Tanzania and the world as a whole.